2-Kidney-1-clip hypertension is not attenuated in mice lacking the transient receptor potential vanilloid type 1 (TRPV1) channel - Stocker, Sean D.; Benoit, Isabella; Sullivan, Jacob B.; Ferreira, Caroline B. (Frontiers in Physiology, 2025)
IntroductionChemical ablation of renal sensory nerves using agonists for transient receptor potential vanilloid-1 (TRPV1) lowers arterial blood pressure (ABP) in multiple experimental models of hypertension. Interestingly, both afferent renal nerve activity and arterial blood pressure were significantly attenuated in male Trpv1−/− rats after 2-kidney-1-clip (2K1C) renovascular hypertension. However, TRPV1 expression in sensory neurons differs across species and is lower in mice versus rats or humans. Therefore, the current study assessed the proportion of TRPV1 in mouse renal sensory neurons and tested whether deletion of TRPV1 altered renovascular hypertension in mice.Methods2K1C surgery was performed by placement of a 0.5mm length of polyetrafluoroethylene tubing around the right renal artery. Experiment 1 quantified the proportion of TRPV1 mouse renal sensory neurons in both sham and 2K1C after a kidney injection of the tracer wheat germ agglutinin conjugated to AlexaFluor 647. Experiment 2 assessed ABP using telemetry in WT and Trpv1−/− mice after 2K1C.ResultsFirst, the majority of retrogradely labeled neurons were located in the ipsilateral T10-L2 dorsal root ganglion and small to medium sized (10-29um diameter). Approximately 60% were TRPV1-positive. Second, 2K1C significantly increased ABP in both male and female WT and Trpv1−/− mice. However, the magnitude of the hypertension was not statistically different between strain and sex. Depressor responses to ganglionic blockade also did not differ between strains and sex.ConclusionThese findings suggest that a subset of renal sensory neurons in the mouse are TRPV1-positive, and renovascular 2K1C hypertension is not attenuated in the Trpv1−/− mouse.